PADMASANA KAJIAN SENI HIAS DAN FUNGSI - I Made Sukanadi (Ars: Jurnal Seni Rupa dan Desain, 2009)
Padmasana is a sacred building for the Hindu people. It is used to worship God. This building is located in the northeast zone of the worship complex (Pura) as the main building. Padmasana building is very closely related to the symbolic values reflected in the name ‘padmasana’ itself, also the shape of the building and its decorative art that adorning the entire padmasana. To reveal these symbolic values, the writer approached the topic using some theories on function that were proposed by some prominent functionalist. The conclusion was that Padmasana functioned, first regiously, second ethically or morally, third aesthetically, fourth economically, and fifth expressively.Keywords: Padmasana, decorative art, function